Morphological evaluation of the application the developed combined medicinal composition on reparative processes at experimental pulpitis (LLC "Endo Press", 2020)
The article presents the results of morphological and structural changes in the pulp using a combination drug composition for the treatment of acute focal pulpitis. The experiment included 13 teeth 5 canines, molars and premolars 8 (6 mongrel dogs between the ages of 2 to 5 years). It is found that the developed medicinal composition possesses specific properties and simultaneously pluripotent in preventing the development of inflammation, enhancing the protective properties of the pulp. In the pulp occurred relief of the inflammatory response and severe intensification of reparative processes.